On-The-Job Training and Earnings Differences by Race and Sex - Duncan, Greg J.; Hoffman, Saul (The Review of Economics and Statistics, 1979)
M OST theoretical and empirical work on the determinants of individual earnings has placed special emphasis on an individual's educational attainment and on his or her years of work experience. Although interpreting the effects of education on earnings is relatively straightforward,1 the proper interpretation of the effects of experience on earnings is much less clear. It is certainly true that earnings tend to rise with years of experience, but the nature of the underlying mechanism that generates that increase is still largely an unresolved issue. An understanding of the way in which experience increases earnings is especially critical for the analysis of wage differentials by race and sex. Previous empirical research has shown that black men and both black and white women have flatter experience-earnings profiles than white males and that differences in the returns to experience account for a large portion of observed wage differences.2 The most widely accepted interpretation of the relationship between experience and earnings is that of the human capital model, which considers years of work experience as a proxy for unobservable investment in on-the-job training.3 According to the human capital model, wage differentials among individuals over the life-cycle are largely the result of differential patterns of investment in human capital, primarily in the form of investments in on-the-job training. Most human capital training models have been developed for the case of training that increases worker productivity in more than one firm (general training) as opposed to specific training that increases productivity in only one firm. It is frequently argued that because women expect to have a less regular pattern of labor force participation, they have a shorter work horizon than otherwise similar men and, thus, they have clear economic incentives to invest in less on-the-job training.4 As a result, women will, in general, have accumulated less human capital than men with the same number of years of experience and, consequently, their returns to experience would be expected to be lower. For black males, lower human capital investment is attributed to discrimination and/or their presumed poorer quality of schooling. Discrimination reduces the value of any potential investment, while poor schooling is thought to increase the costs of acquiring training.5 An alternative view of the earnings-experience relationship draws on models of labor market segmentation.6 These models differ from the human capital model primarily in their focus on the characteristics of jobs and job markets, rather than the characteristics of individuals. Earnings are thought to be largely determined by the labor market in which an individual works rather than the skills (or human capital) he or she possesses. Training itself is viewed as being largely technologically determined by the design of jobs, so that a specified amount of training is intrinsic in any given job. An individual acquires training by first gaining access to a job that provides training; that is, jobs and job markets intercede between an individual and investment in on-the-job training. Segmented market theorists usually argue that because hiring decisions involve a considerable amount of subjective input there is ample opportunity to practice discrimination. They cite entry level discrimination as a major institutional barrier between the primary and secondary sector, Received for publication January 17, 1978. Revision accepted for publication November 1, 1978. * Institute for Social Research and University of Michigan, and University of Delaware, respectively. 1 A recent review of this literature is given in Blaug (1976). 2 For example, see Mincer and Polachek (1974), Blinder (1973). 3The basic references are Becker (1964), Ben-Porath (1967), and Rosen (1972). 4 Mincer and Polachek (1974); Johnson and Stafford (1974). 5 The effect of discrimination on investment varies in different versions of the human capital model. It has no effect in a Ben-Porath type model, but reduces optimal investment in Rosen's model. 6 This model was popularized by Doeringer and Piore (1971).